1995
DOI: 10.1063/1.360376
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties of SrS:Ce3+

Abstract: SrS:Ce is an intensively investigated phosphor due to its blue-green electroluminescence, which shows efficient blue emission after filtering. Recently reported devices based on this material have demonstrated a luminous efficiency of 1.6 lm/W. The luminescence properties of SrS:Ce,X (X=Na or Cl) have been studied on powders and thin films. It is shown that a high density of traps in SrS:Ce,X occurs. The interaction of Ce3+ with traps gives rise to a phosphorescence. An energy transfer from Ce3+ to traps is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 9 publications
7
26
0
1
Order By: Relevance
“…1). High doping shows the well known concentration quenching of the luminescence due to an enhanced interaction between the centres and the disturbed lattice periodicity [15].…”
Section: Resultsmentioning
confidence: 99%
“…1). High doping shows the well known concentration quenching of the luminescence due to an enhanced interaction between the centres and the disturbed lattice periodicity [15].…”
Section: Resultsmentioning
confidence: 99%
“…A double insulated CaS:Ce thin-film electroluminescent (EL) device emitting a bright green EL due to the Ce 3 þ luminescent centre has been reported [7]. SrS doped by Ce 3 þ and co-doped by Pb 2 þ or Cl À , Na þ also gained attention mainly due to possibility of being used as thin films in electroluminescence devices [8][9][10]. Codoping of SrS:Ce by other RE 3 þ ions and their impact on the transient emission processes are discussed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…The blue shift in PL has been observed for SrS:Ce thin film nanophosphors, but the PL output was found to be almost six times lower than that from the powder phosphors. Huttl et al [27] have also reported that PL yield for SrS:Ce,Cl thin films is around five times lower than that for powders.…”
Section: Resultsmentioning
confidence: 98%